(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2023)
Abstract This research aims to define the roles of auditors by clarifying the concept and risks of cyber security in protecting information and financial data in economic units. Najaf, Babylon and Karbala, then the results were analyzed and the results were presented and analyzed to show that adopting cyber security improves the quality of reports Finance through what it achieves in displaying information with credibility and transparency, in a way that suits the needs of users, and cyber security has a role in managing economic resources more effectively to obtain benefits that would have been lost in the event of any electronic attacks. This study concluded with the following conclusions: There is an impact on the privacy of customer data, risk management, and that the privacy of customer data had the greatest impact on the quality of financial reports.